Strong couplings and form factors of charmed mesons in holographic QCD - Ballon-Bayona, Alfonso [UNESP]; Krein, Gastão [UNESP]; Miller, Carlisson [UNESP] (American Physical Society (APS), 2017)
We extend the two-flavor hard-wall holographic model of Erlich, Katz, Son, and Stephanov [Phys. Rev. Lett. 95, 261602 (2005)PRLTAO0031-900710.1103/PhysRevLett.95.261602] to four flavors to incorporate strange and charm quarks. The model incorporates chiral and flavor symmetry breaking and provides a reasonable description of masses and weak decay constants of a variety of scalar, pseudoscalar, vector, and axial-vector strange and charmed mesons. In particular, we examine flavor symmetry breaking in the strong couplings of the ρ meson to the charmed D and D∗ mesons. We also compute electromagnetic form factors of the π, ρ, K, K∗, D and D∗ mesons. We compare our results for the D and D∗ mesons with lattice QCD data and other nonperturbative approaches.